The Impact of Multimedia Feedback in Blended Learning Environments on University Students’ Programming Skills - Rebecca A. Foster; Katherine L. Wood; Matthew H. Evans (Research and Advances in Education, 2024)
This study investigates the impact of multimedia feedback on university students’ programming skills within a blended learning environment in the United Kingdom. A quasi-experimental design was employed, involving 120 undergraduate students divided into experimental and control groups. The experimental group received multimedia feedback, including screencast videos, annotated coding examples, and interactive quizzes, while the control group received traditional written feedback. Quantitative data from pre-tests and post-tests showed that the experimental group demonstrated a 33.3% increase in programming skills, compared to a 22.5% increase in the control group. The experimental group also exhibited a 35% reduction in errors and a 20% reduction in task completion time. Qualitative data from student interviews and open-ended survey responses revealed increased engagement, understanding, clarity, motivation, and confidence among students who received multimedia feedback. The study highlights the transformative potential of multimedia feedback in enhancing programming education and suggests practical implications for educators and policymakers. Recommendations for future research include exploring the long-term impact, scalability, and applicability of multimedia feedback across different educational contexts and disciplines.